Dampak Rasio Profitabilitas dan Rasio Solvabilitas terhadap Harga Saham pada Perusahaan Retailing - Astuti, Nita (CV. Kalimasada Group, 2024)
The aim of this research is to determine the effect of profitability ratios (return on assets and return on equity) and solvency ratios (debt to equity ratio) on stock prices. The objects of the research are retailing sector companies that are listed consistently on the Indonesia Stock Exchange for the period 2018 - 2022. This type of research is quantitative research, with a sampling technique using purposive sampling, and according to the sample criteria, 8 companies were selected that met the criteria with total data n= 40. Statistical testing uses multiple regression analysis using SPSS version 23 statistical software. The results of the study partially show that the debt to equity ratio (solvency ratio) variable has a negative and significant effect on stock prices, while the return on asset ratio and return on equity ratio (profitability ratio) variables has no effect on share prices. And simultaneously the variables return on asset ratio, return on equity ratio and debt to equity ratio influence stock prices.